Mothers experiences of genetic counselling in Johannesburg, South Africa - Morris, Megan (My University, 2014)
Genetic counselling is an expanding profession, with many services now being offered in multicultural settings. The way in which individuals respond to genetic disorders varies greatly between countries, socio-economic groups, families, communities, religions and cultural groups. Together, these perspectives may influence how people experience genetic counselling with regard to satisfaction of the service, understanding heritability, communication, support and general healthcare provision. To address these issues standardised healthcare and genetic counselling models may need to be adjusted to prevent disparities in healthcare communication for different communities across the globe. South Africa provides a unique setting for genetic counselling because of the rich multicultural and linguistic diversity, as well as the many health and socioeconomic challenges that the country faces. Due to these diversities and challenges, further exploration into individuals‟ experiences of genetic counselling in South Africa is required to gain insight into the service needs for individuals.
Keywords: Genetic Counseling; Mothers